A Tale of a Traumatized Mother in “Liwang 2006” - Pokharel, Badri Prasad (Interdisciplinary Journal of Management and Social Sciences, 2021)
Nepal has been known a land of peace. But, due to various factors, this country has witnessed many facets of violence in different parts. A decade long conflict between the rebel and national security force that devastated the country’s economic, political, social and cultural discourse has become an integral part for creation of new genres for readers and writers. This mnemonic past along with other historical details, as an integrative focal point has induced creative mind to generate the lifelike situation i.e. disappearance of Purnaman, characters i.e. Dilsara, Bainsamali, Chitra Bahadur Punmagaretc along with their creative artifacts. Rajkumar Dikpal, a prolific storyteller in Nepali literature edifies these characters in his story “Liwang 2006”in th the background of ten years long Maoist insurgency. It unfolds an old mother who has lost her only son who used to dream of her only happiness. And the trauma of these commoners is a means to represent the political scenario of the nation.